Penerapan Pembelajaran IPS Dengan Media Ular Tangga Untuk Meningkatkan Minat Belajar Siswa Kelas IV SDN Kecamatan Prambon Nganjuk - Permana, Erwin Putera; Imron, Ilmawati Fahmi (Efektor, 2016)
From the observation results of research on class IV SDN Prambon Nganjuk, found some obstacles in learning the practice of IPS. Constraints of the teacher in the learning infrastructure is inadequate in elementary school and the teachers do not use the media to learn the lessons. Constraints of the students are students who have not been actively involved in learning social studies class. This study aims to describe the activities conducted teacher in learning activities using the media snake ladder, describe the students in learning activities using the media ladder snake, described the improvement of student learning through the media interest in snakes and ladders and describe the constraints of students through the medium of snakes and ladders in teaching social studies. In this research use classroom activities reseach. Subject and location of reseach is student of fourth class SDN Tanjungtani 3 Prambon Nganjuk, which consist of 27 students, 15 male students and 12 female students. In this reseach, reseacher using reseach instrument as data processing activities for teacher, student activities for students, students interest and interviews. Based on the results of learning activities using the media snakes and ladders to get a very good response from students. This can be evidenced teacher observations and student activities, teacher observations in cycle III reached 87.5% and the observation of the student activity a score 85.7%. Besides the interest of the students show great interest in, this proved to achieve a score of 34.3. So snakes and leader media use to learning activities in class for study increase interest.